Language brokering and differentiated opportunities for participation - Harjunpää, Katariina (Calidoscópio, 2021)
In a multilingual situation where some participants do not speak or understand one of the languages used, the participants need to strike a balance between the language choice and the restrictions it creates for opportunities to participate in the interaction. In this conversation analytic study, I examine how participants manage differentiated opportunities for participation in asymmetrically multilingual interactions during instances of language brokering, and the extent to which brokering draws the recipient into the conversation. Focusing on cases without verbal initiations of repair or requests for brokering, the paper argues that participants’ embodied displays of recipiency toward a main speaker, whose talk they cannot (fully) understand, as well as embodied displays of disengagement from the conversation, can serve to “recruit” linguistic assistance. The analyses demonstrate how the design of the brokering turns conveys the broker’s orientations to the recipient’s participation status, and how it can warrant their further focal or peripheral participation. The study thereby demonstrates how participants multimodally negotiate forms of participation and their accountability. Although language brokering is done only occasionally and includes great variation in terms of how prior talk is translated, the ways of brokering are not random but result from an interactional organization of social action and participation. Keywords: Language brokering; Peripheral Participation; Gaze.